REFORMASI BIROKRASI PADA DINAS PERHUBUNGAN KABUPATENLEBAK PROVINSI BANTEN - Rusito Rusito (NIAGARA Scientific Journal, 2022)
This research has a starting point from the problems that indicate the slow pace of changes in bureaucratic reform at the Department of Transportation, Lebak Regency, Banten Province. The purpose of this study is to gain a deep understanding of the areas of change in bureaucratic reform. The references used are eight areas of change in bureaucratic reform in the Menpan RB guidebook (2018: 9). The study used a qualitative research designwith a qualitative descriptive analysis method. The results of the study concluded that bureaucratic reform was carried out through eight areas of change, namely changes in organization, management, human resources of the apparatus, laws and regulations, accountability, public services and organizational culture.